PENGARUH PENYULUHAN IMUNISASI TERHADAP PENINGKATAN PENGETAHUAN DAN KEPATUHAN IBU TENTANG IMUNISASI DASAR LENGKAP PADA BAYI SEBELUM USIA 1 TAHUN DI KECAMATAN KARANGMONCOL - Wilis Sukmaningtyas; Iis Setiawan (Universitas Harapan Bangsa Purwokerto, 2015)
Immunization program has been developed. It was done during prevention of some disease that preventable by immunization (PD31),i.e.tuberculosis, diphtheria, pertusis, measles, polio, tetanus, and hepatitis B.After data was evaluated, result known that there are still many areas with undertarget immunization, even there is too extreme slack. One of efforts done ispromotion program; such activates illumination about importance ofimmunization for babies and school-children and also childbearing age andpregnant mother, so public knowledge about immunization will motivate them to care and follow immunization without any worried. Purpose of this study is to know the impact of immunization illumination for mother’s knowledge and attitude increase about completebasic immunization for 1 year old baby. It was a comparative study withposttest-only approach and control group experimental design, which is experiment among 2 groups, treated group and untreated group as controller.Sample size was determined by cluster random sampling using proportionestimation statistical of population 60 toddler’s mother.Data was collected using questionnaire about mother’s knowledge and attitude about complete basicimmunization. It was firstly tested by validity and reliability test before. Analysisused was Two Independent Sample t-test by SPSS for Windows programversion 17. The result of knowledge achieved t-value = 5.387 with probability0.000, whereas attitude achieved t-value = 11.495 with probability 0.000.According to analysis result, it is concluded that there is impact of immunizationillumination for mother’s knowledge increase about complete basic immunization.Beside that, there is also impact of immunization illumination for mother’sattitude about complete basic immunization to become better. Key words : Promotion, Knowledge and Attitude